ANALISIS PENERAPAN DISIPLIN KERJA DAN MOTIVASI DALAM MENINGKATKAN KINERJA PEGAWAI PADA DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DI KOTA BOGOR - Pramestianingrum, Melinda; Andi, Dede (Journal of Research and Publication Innovation, 2024)
This study aims to determine work discipline, employee motivation applied by the office of community empowerment of women and child protection of bogor city and to find out strategies for improving work discipline and motivation in improving employee performance at the office of community empowerment of women and child protection of bogor city. this research is descriptive qualitative research with a phenomenological approach. Based on the results of the interviews, the majority stated that the discipline shown by management had a big impact in encouraging other employees to imitate it. Based on the interview results, the majority stated that the ability to complete tasks quickly and on time is a sign of work motivation. Based on the results of the interviews, the majority stated that the approach to improving work discipline and motivation in improving employee performance at the Bogor City Office of Community Empowerment of Women and Child Protection involves creating a schedule of activities, using various schedules to maintain order, and creating a list of tasks based on deadlines. The implementation of these strategies assisted employees in managing time more efficiently, improving accuracy in completing tasks, and ultimately improving overall performance.